Hukum Islam dan Kesetaraan Jender di Indonesia - Salim, M. Arskal (Studia Islamika, 2003)
This book is an ethnographic exploration of how Muslim people consider and resolve their daily difficulties in relation to law, religion and a notion of an ideal equality in pluralistic Indonesia. The main themes of this book involve public reasoning; interpretations, justifications, find arguments about various norms and rules related to marriage, divorce and inheritance. Bowen discusses diverse topics such as access to land, religious identity, women's rights, respect for ancestors, modernization, the rules of law, and the problems of holding together a nation. Gender analysis, equal rights, the relationship between men and women, and the interrelationship between religions, local tradition and universal norms were the key considerations in this book.DOI: 10.15408/sdi.v10i3.627